(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Surface Coal Exploitation (SCE) predominantly relies on both continuous and discontinuous technologies, notably the bucket wheel and the truck and shovel methods. Specifically, the bucket wheel (continuous) method is optimal for expansive mines with favourable geological conditions, whereas the truck and shovel (discontinuous) method is better suited for mines with intricate geology, including smaller-scale operations. On a global scale, surface coal mining practices in Europe diverge somewhat from those in Australia and the USA. While shovel and truck configurations predominate in Australia and the USA, European nations predominantly employ bucket wheel excavators. Kosovo also boasts a rich heritage and proficiency in employing continuous technologies. This study elucidates the variations in coal production costs across different countries utilizing distinct technologies under diverse geological conditions, thereby enabling an insightful analysis of individual mine performance. The cost of coal production (/t), accompanied by respective stripping ratios (SR), stands at 18.7 (SR, 3:1) in Kosovo, 13.8 (SR, 1.3:1) in the USA, and 7.37 (SR, 4:1) in Germany. The research underscores that the cost and productivity of surface coal production are contingent upon the alignment of technology with the geological and geometrical attributes of the mine. The comparative methodology, augmented by a comprehensive literature review and in-situ analysis, forms the backbone of this research. Concurrently, Excel-Pivot Chart analysis, in conjunction with Matlab, serves as the computational engine for data processing and analysis.